Implementation of Gesture Recognition Technology for Self-Education Service Platform - Makahaube, Stella; Sambul, Alwin M.; Sompie, Sherwin R.U.A. (Jurnal Teknik Informatika, 2021)
Gesture recognition technology is a technology used to identify object movements that have been recognized by machines, computers and then become commands. This study aims to be able to reduce direct physical contact, which can minimize transmission. The research with the title "Implementation of Gesture Recognition Technology at the Self-Education Service Platform". This study uses Mediapipe so that the hand gesture object can be recognized. Gesture recognition technology identifies gesture objects or form objects, namely hand gestures, hand gestures that will later become input media. Especially during a pandemic like this, many activities in human life are now adapting again to make physical contact less or touch less to reduce transmission through physical contactTeknologi gesture recognition merupakan teknologi yang digunakan untuk mengidentifikasi gerakan objek yang telah dikenali oleh mesin, komputer menjadi perintah. Penelitian ini memiliki tujuan untuk bisa mengurangi kontak fisik secara langsung, yang bisa meminimalisir terjadi penularan. Penelitian yang mengangkat judul â€œImplementasi Teknologi Gesture Recognition Pada Anjungan Layanan Mandiri Edukasiâ€. Penelitian ini menggunakan Mediapipe agar supaya objek hand gesture dapat dikenali. Teknologi gesture recognition mengidentifikasikan objek gesture atau objek bentuk yaitu hand gesture Gerakan tangan yang nantinya akan menjadi media input. Apalagi pada saat pandemi seperti ini banyak kegiatan dalam kehidupan manusia yang sekarang mengadaptasi lagi untuk membuat kontak fisik berkurang atau touch less untuk mengurangi penularan melalui kontak fisik